Tim-3 Regulates Tregs' Ability to Resolve the Inflammation and Proliferation of Acute Lung Injury by Modulating Macrophages Polarization. Issue 4 (October 2018) - Liu, Xiandong; Jiang, Sen; Zhang, Qian; Xu, Shumin; Bao, Xiaowei; Cao, Wei; Bai, Jianwen; Tang, Lunxian
Abstract : ABSTRACT: We recently reported that CD4 + CD25 + regulatory T cells (Tregs) contributed to the recovery of patients with acute lung injury (ALI) by upregulating T cell immunoglobulin and mucin-domain containing-3 (Tim-3). However, the molecular mechanism by which Tim-3 regulates Tregs' function in the resolution and fibroproliferation after ALI remains unknown. In this study, we adoptively transferred Tim-3 + Tregs or Tim-3 − Tregs into lipopolysaccharide -induced ALI mice model. Data demonstrated that Tim-3 + Tregs not only decreased indices of lung inflammation and injury but also mitigated lung fibrosis after ALI. Furthermore, we observed that the transfer of Tim-3 + Tregs led to M2-like macrophage differentiation as demonstrated by significantly upregulated levels of M2-associated phenotypic markers as well as downregulated expressions of M1-related markers in both the profibrotic lung tissue and sorted pulmonary monocytes after ALI. In addition, cytokines such as interleukin (IL)-10 and IL-4 were also upregulated in lung tissues after Tim-3 + Tregs transferring. In vitro experiments further demonstrated that cell-contact cocultures with Tregs lacking Tim-3 presented decreased polarization of M2-like macrophages partially mediated by a decreased expression and function of STAT-3. Therefore, these data demonstrate a previously unrecognized function of Tim-3 on Tregs in their ability to repress the fibroproliferation of ALI by inducing alternative macrophages polarization. Moreover, the data highlight that Tim-3 + Tregs-mediated induction of M2-like macrophages may be a novel treatment modality with transitional potential.